TYPES OF MOTHER LANGUAGE LESSONS ACCORDING TO THE PURPOSE - Ashurova Shoira Shodiyevna (Journals Park Publishing, 2023)
The native language lessons are divided into four types according to the purpose: teaching and strengthening of new material, repeating what has been learned and creating skills, lessons summarizing knowledge and skills, and testing knowledge and skills.
Keywords: types of lessons, reinforcement, formation of skills, generalization, examination, method.